Effects of inspiratory muscle training in patients with hypertension: a meta-analysis - Zheng, ShuQi; Zhang, Qi; Li, ShuiYan; Li, Shilin; Yao, Qiuru; Zheng, Xiaoyan; Li, Gege; Zeng, Yuting; Chen, Ling; Chen, Shuping; He, Longlong; Zou, Jihua; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective: To explore the effects of inspiratory muscle training (IMT) on hypertension and provide guidance for its clinical application as an auxiliary approach. Methods: Articles published prior to July 2022 were searched in The Cochrane Library, Web of Science, PubMed, Embase, Medline, CNKI, and Wanfang database. Included were randomized controlled studies that used inspiratory muscle training to treat individuals with hypertension. The weighted mean difference was computed using the Revman 5.4 software. In individuals with hypertension, the effects of inspiratory muscle training on systolic blood pressure, diastolic blood pressure, heart rate, and pulse pressure were compared and studied. Results: There were found to be eight randomized controlled trials totaling 215 patients. According to a meta-analysis, the IMT reduced the systolic blood pressure (WMD: −12.55, 95% CI: −15.78, −9.33), diastolic blood pressure (WMD: −4.77, 95% CI: −6.00, −3.54), heart rate (WMD: −5.92, 95% CI: −8.72, −3.12), and pulse pressure (WMD: −8.92, 95% CI: −12.08, −5.76) in patients with hypertension. In subgroup analysis, low-intensity IMT showed a better reduction in systolic blood pressure (WMD: −14.47, 95% CI: −17.60, −11.34), diastolic blood pressure (WMD: −7.70, 95% CI: −10.21, −5.18). Conclusion: In individuals with hypertension, IMT significantly lowered their blood pressure, heart rate, and pulse pressure. In subgroup analysis, low-intensity IMT was more effective in regulating blood pressure than medium-high-intensity inspiratory muscle training.